Palladium catalysed elaboration of codeine and morphine - Davies, S; Goodwin, C; Pyatt, D; Smith, A (2001)
Palladium catalysed coupling reactions of 6-O-tert-butyldimethylsilyl-1-bromocodeine and 6-O-tert-butyldimethylsilyl-3-trifluoromethylsulfonylmorphine allow a range of substituted analogues of codeine in the 1-position and morphine in the 3-position to be efficiently and selectively prepared.